Kajian Historis Dinamika Sikap Gereja terhadap Olahraga - Gandi Wibowo; Denny Andreas; Ivon Rahmani (LPPM STT Baptis Kalvari, 2023)
The church has a dynamic view of sport from a historical perspective. The celebration of Istmian games in the Greek and Roman eras gave a perspective that sport in ancient culture was part of the worship of the gods. Even so, the Apostle Paul actually accommodated sports matches as an illustration of the struggle for the faith of believers in his message to the congregation in Corinth. At that time Corinth regularly held Istmian games as a paganistic worship of Poseidon. The church fathers had pros and cons views on sports activities and tournaments. But then the paradigm shift became positive as the influence of polytheism and Hellenism receded in the celebration of sport. This research was conducted qualitatively with a historical theological approach. Sports actually have a positive impact on physical health. It also trains teamwork and communication, and forms a disciplined and sporty personality.